First identification of the family Amathillopsidae Pirlot, 1934 (Crustacea, Amphipoda, Gammaridea) in the Caribbean Sea, with the description of a new species - Varela, Carlos (2015)
A new species of the genus Amathillopsis is described. Main characteristics include the absence of eyes, accessory flagellum 1-segmented, distally emarginate telson, medial dorsal spinous process on pereionites 4-7, pleonites 1-3 and urosomite 1. This is the first record of a species of the family Amathillopsidae Pirlot, 1934 for the Caribbean Sea.